Intermittent θ burst stimulation modulates resting-state functional connectivity in the attention network and promotes behavioral recovery in patients with visual spatial neglect. Issue 17 (7th December 2016) - Cao, Lei; Fu, Wei; Zhang, Yanming; Huo, Su; Du, JuBao; Zhu, Lin; Song, Weiqun
Abstract : Functional connectivity changes in the attention network are viewed as a physiological signature of visual spatial neglect (VSN). The left dorsal lateral prefrontal cortex (LDLPFC) is known to initiate and monitor top–down attentional control and dynamically adjust behavioral performance. This study aimed to investigate whether increasing the activity of the LDLPFC through intermittent θ burst stimulation (iTBS) could modulate the resting-state functional connectivity in the attention network and facilitate recovery from VSN. Patients with right hemisphere stroke and VSN were randomly assigned to two groups matched for clinical characteristics and given a 10-day treatment. On each day, all patients underwent visual scanning training and motor function training and received iTBS over the LDLPFC either at 80% resting motor threshold (RMT) or at 40% RMT before the trainings. MRI, the line bisection test, and the star cancelation test were performed before and after treatment. Patients who received iTBS at 80% RMT showed a large-scale reduction in the resting-state functional connectivity extent, largely in the right attention network, and more significant improvement of behavioral performance compared with patients who received iTBS at 40% RMT. These results support that the LDLPFC potentially plays a key role in the modulation of attention networks in neglect. Increasing the activity of the LDPLPFC through iTBS can facilitate recovery from VSN in patients with stroke. Abstract : Supplemental Digital Content is available in the text.